Constructing Customized Multimodal Phantoms Through 3D Printing: A Preliminary Evaluation - Qiu, Jianfeng; Hou, Kun; Dyer, Brandon A.; Chen, Jyh-Cheng; Shi, Liting; Sun, Yong; Xu, Longchun; Zhao, Huihui; Li, Zhengmei; Chen, Tiao; Li, Minghui; Zhang, Fuquan; et al. (Frontiers in Physics, 2021)
Purpose: To develop a method for constructing customizable, multimodal quality control (QC) imaging phantoms based on 3D printing technology. Materials and Methods: Four phantoms were designed and constructed through 3D-printing technology using three unique printing materials. Physical parameters of the 3D-printed materials were evaluated, including density, shore hardness, porosity, deformation temperature, computed tomography (CT) number, absorption coefficient, and printing accuracy. Imaging performance of the phantoms was studied using MRI, CT, PET/MR, and PET/CT, and compared with conventional/commercial phantoms. imaging assessments included high contrast resolution, low contrast resolution, uniformity, deformation, SNR, slice accuracy/slice thickness, location accuracy/laser alignment, CT number, relaxation time, and registration. Results: All three printing materials have a shore hardness of 90. The physical densities of these materials are 1.15 g/ cm3, 0.76 g/ cm3 and 1.27 g/ cm3, respectively. The porosities are 9.09%, 6.81%, and 18.56%, respectively. The threshold temperature of deformation for the three materials is greater than 105C, which is higher than that of PMMA and silica gel. Imaging scans of the constructed phantoms for single modality scanners (MRI and CT) and dual-modality scanners (PET/MRI and PET/CT) were compared with those of the commercial phantoms. The standard deviation of the HU value uniformity test was less than 3 HU for CT scans. Conclusion: 3D-printed medical imaging phantoms allow for rapid, customized phantom fabrication for clinical situations across single and dual modality imaging platforms. Further imaging parameter analysis is underway to provide more quantitative evaluation of the proposed phantoms.